Entreprises transnationales, exportations de produits manufacturés et emploi dans les pays moins développés - Helleiner, G. (L'Actualité économique, 1977)
AbstractThis article is an abridged version of a document presented by the author at the World Conference on Employment held in Geneva in 1976. The study deals successively with the role of transnational enterprises in the production (and marketing) of exports to other LDC's and developed countries, the composition of these exports as well as their short and long-term effects on economic development, government revenues, employment and income. Outlining difficulties with which the LDC's will be confronted in their promotion of the export sector, the author puts forward several policy areas where active negotiations between developed countries and LDC's could lead to substantial improvement.